Allelic differences of clustered terpene synthases contribute to correlated intraspecific variation of floral and herbivory‐induced volatiles in a wild tobacco. Issue 3 (12th July 2020) - Xu, Shuqing; Kreitzer, Christoph; McGale, Erica; Lackus, Nathalie D.; Guo, Han; Köllner, Tobias G.; Schuman, Meredith C.; Baldwin, Ian T.; Zhou, Wenwu
Summary: Plant volatile emissions can recruit predators of herbivores for indirect defense and attract pollinators to aid in pollination. Although volatiles involved in defense and pollinator attraction are primarily emitted from leaves and flowers, respectively, they will co‐evolve if their underlying genetic basis is intrinsically linked, due either to pleiotropy or to genetic linkage. However, direct evidence of co‐evolving defense and floral traits is scarce. We characterized intraspecific variation of herbivory‐induced plant volatiles (HIPVs), the key components of indirect defense against herbivores, and floral volatiles in wild tobacco Nicotiana attenuata . We found that variation of ( E )‐β‐ocimene and ( E )‐α‐bergamotene contributed to the correlated changes in HIPVs and floral volatiles among N. attenuata natural accessions. Intraspecific variations of ( E )‐β‐ocimene and ( E )‐α‐bergamotene emissions resulted from allelic variation of two genetically co‐localized terpene synthase genes, NaTPS25 and NaTPS38, respectively. Analyzing haplotypes of NaTPS25 and NaTPS38 revealed that allelic variations of NaTPS25 and NaTPS38 resulted in correlated changes of ( E )‐β‐ocimene and ( E )‐α‐bergamotene emission in HIPVs and floral volatiles in N. attenuata . Together, these results provide evidence that pleiotropy and genetic linkage result in correlated changes in defenses and floral signals in natural populations, and the evolution of plant volatiles is probably under diffuse selection.